MOLECULAR ANALYSIS OF SOME FORENSICALLY SIGNIFICANT DIPTERANS ASSOCIATED WITH DECOMPOSING PIG (SUS SCROFA) CARCASS IN IWO SOUTH-WESTERN NIGERIA USING THE COI GENE - Olatubi, Iyabo Victoria; Muse, Wasiu Adesola; Adelabu, Olusesan Adeyemi; Awodiran, Olufemi Michael; Okoh, Anthony Ifeanyi (Malaysian Journal of Science, 2024)
Identification of many forensically important insects has been achieved using morphological keys with only a few relying on molecular techniques. Yet, information regarding the molecular identification of Dipteran flies from sub-Saharan Africa is scarce. Therefore, this study used the COI gene to analyze fly specimens collected from decomposing pig (Sus scrofa) carcasses in Iwo South-Western Nigeria. Several batches of eggs from carcasses were reared to adults and preserved in 75% ethanol for subsequent identification using molecular techniques in triplicate. A total of 450 bp sequences was obtained from BLAST analysis of the samples from the population, which has led to the identification of four families consisting of five species with the following breakdown: Sarcophaga africa (95.4%), Chrysomya putoria (99.1%), Chrysomya inclinata (98.3%), Tricogena rubricosa (89.6%), and Chirosia flavipennis (88.8%). The phylogenetic analysis identified Chrysomya chloropyga (AY139694) as the same as C. putoria and S. africa as the same as Sarcophaga cruentata, suggesting them as sister species. This study concluded that T. rubricosa and C. flavipennis are implicated in carrion decomposition, which provides crucial insights for forensic investigations